2016
DOI: 10.1016/j.dib.2016.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Glycomic and sialoproteomic data of gastric carcinoma cells overexpressing ST3GAL4

Abstract: Gastric carcinoma MKN45 cells stably transfected with the full-length ST3GAL4 gene were characterised by glycomic and sialoproteomic analysis. Complementary strategies were applied to assess the glycomic alterations induced by ST3GAL4 overexpression. The N- and O-glycome data were generated in two parallel structural analyzes, based on PGC-ESI-MS/MS. Data on glycan structure identification and relative abundance in ST3GAL4 overexpressing cells and respective mock control are presented. The sialoproteomic analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
20
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 9 publications
3
20
0
Order By: Relevance
“…Our results showed that the ST3GAL4 cell model displays a significant increase of α2,3-sialylation concomitant to a decrease of α2,6-sialylation. These results are in agreement with glycomic data previously reported [12,34]. In addition, a significant decrease in fucosylation, presumably outer arm fucosylation, was found as detected by Aleuria aurantia lectin (AAL).…”
Section: Overexpression Of α23-sialyltransferases Results In Differesupporting
confidence: 92%
See 1 more Smart Citation
“…Our results showed that the ST3GAL4 cell model displays a significant increase of α2,3-sialylation concomitant to a decrease of α2,6-sialylation. These results are in agreement with glycomic data previously reported [12,34]. In addition, a significant decrease in fucosylation, presumably outer arm fucosylation, was found as detected by Aleuria aurantia lectin (AAL).…”
Section: Overexpression Of α23-sialyltransferases Results In Differesupporting
confidence: 92%
“…Previous work disclosed that MET and RON downstream signaling is more activated upon overexpression of ST3GAL4 [11,12]. The expression of the SLeX epitope was detected by antibody-based assays, however, a detailed glycomic analysis by MS made clear that the most striking alteration in ST3GAL4 model was the general increase of α2,3-sialylation [34]. Increased sialylation on RTKs have been shown to play a role in tumor progression [11,41].…”
Section: Discussionmentioning
confidence: 99%
“…The upregulation of ST3GAL4 in MKN45 leads to an increase in a2,3 sialylation and a decrease in a2,6 sialylation on N-glycans and significantly decreases the amount of bisected structures [45,50]. On O-glycans, ST3GAL4 leads to the earlier termination due to the increase in one specific structure: the di-sialylated core 2 structure [45,50]. Both the ST6GALNAC1 overexpression and the COSMC deletion induce alteration on O-glycans and lead to an upregulation of STn by two differential mechanisms [38,41].…”
Section: Discussionmentioning
confidence: 99%
“…1C,D) [30]. The M3 and ST3 models have previously been characterized by O-glycomic analysis and thus allowed us to estimate the induced alterations [45,50]. In this regard, the major O-glycans of M3 with the composition Hex-NAc 5 Hex 5 Neu5Ac 2 and HexNAc 4 Hex 4 Neu5Ac 2 , with the average masses of 2427.2 and 2061.9 Da, respectively, were altered in the ST3 model to HexNAc 2 Hex 2 Neu5Ac 2 , with an average mass of 1331.2 Da.…”
Section: Truncation Of O-glycans Affects the Molecular Weight Of Cd44mentioning
confidence: 99%
“…Therapeutically, ST6GAL1 can be used to predict response to EGFR/HER2 inhibitors in ovarian cancer cells [34]. Similarly, ST3GAL4 is also upregulated in cancer, and is associated with poor prognosis; metastasis and the synthesis of Sialyl Lewix X (sLe X ) in gastric carcinoma [18,35]. ST3GAL6 is also linked to the synthesis of sLe X and the generation of E-selectin ligands [36,37].…”
Section: Glycosyltransferase and Glycosidase Enzymesmentioning
confidence: 99%